Novel Affordable, Reliable and Efficient Technologies to Help Addressing the Water-Energy-Food Nexus - Meneguzzo, Francesco; Zabini, Federica; Albanese, Lorenzo; Crisci, Alfonso (European Journal of Sustainable Development, 2019)
Improving the food system sustainability and security is becoming an urgent global challenge. In this regard, one of the most effective routes is the shift of the human diet toward healthier and more sustainable consumption, involving in particular the prevalence of plant-based raw food materials. Controlled hydrodynamic cavitation (HC) technologies could help considerably in this transition. HC techniques are gaining increased scientific interest, and are quickly spreading across a wide range of technical fields, recently showing surprising performances with biological raw materials related to the food, agricultural and forestry sectors and resources. HC processes enjoy recognized advantages in the acceleration of the processing steps of plant-based food, the extraction of valuable bioactive compounds, the reduction and the valorization of waste streams, as well as the superior efficiency in resource use, energy consumption, process yield, and exergy balance than competing processes. Thus, HC is very promising candidate to help addressing the water-energy-food nexus, and, ultimately, sustainability. Findings obtained from direct experimental trials and recent literature concerning the applications of HC to food processing, provide a strong basis for novel investigation aimed at standardization, starting from the identification of the most suitable devices and the optimal processing parameters, eventually oriented to further spreading of HC applications.